2001
DOI: 10.1079/bjn2001356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high temperature on feeding behaviour and heat production in group-housed young pigs

Abstract: To assess the acclimation of pigs to heat stress, the effects of high (338C) or thermoneutral (238C) constant temperatures on feeding behaviour and components of energy balance were studied in group-housed young pigs. Three groups of five pigs were used at each temperature. After 1 week of adaptation, voluntary feed intake (VFI) and heat production (HP) were recorded for thirteen consecutive days. Animals were fed ad libitum. Fasting HP was measured on the last day. Average initial body weights (BW) were 21´4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
105
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 25 publications
12
105
1
6
Order By: Relevance
“…Effects of the heat stress on the electron transport chain gene expression Our performance results are in accordance with several studies which demonstrated negative impacts of high temperatures on pig performance in growing and finishing pigs (Quiniou et al, 2000;Collin et al, 2001a;Renaudeau et al, 2012), including reduced voluntary daily feed intake and daily weight gain (Collin et al, 2001b;Kerr et al, 2003;Renaudeau et al, 2011). In contrast, very little has been published on the effects of the thermal environment on the regulation of genes involved in energy metabolism.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Effects of the heat stress on the electron transport chain gene expression Our performance results are in accordance with several studies which demonstrated negative impacts of high temperatures on pig performance in growing and finishing pigs (Quiniou et al, 2000;Collin et al, 2001a;Renaudeau et al, 2012), including reduced voluntary daily feed intake and daily weight gain (Collin et al, 2001b;Kerr et al, 2003;Renaudeau et al, 2011). In contrast, very little has been published on the effects of the thermal environment on the regulation of genes involved in energy metabolism.…”
Section: Discussionsupporting
confidence: 76%
“…Several studies have demonstrated that high temperatures have negative effects on the performance of pigs during most phases of production (Quiniou et al, 2000;Collin et al, 2001a;Renaudeau et al, 2011), but there is little information about the changes in muscular energy metabolism in heat-stressed pigs (Rinaldo and Dividich, 1991;Collin et al, 2001b) or on the interaction between dietary levels of aP and the thermal environment to which the animals are submitted.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that elevated temperatures affect nutrients digestibility when the range of temperature between thermoneutral and hot treatment is greater than 88C. Similarly, Collin et al (2001b) observed an increase of DM, N and energy digestibility coefficients between 238C and 338C in temperature-acclimated young pigs. In this study, the effect of temperature on nutrient digestibility was not significant when pigs at 238C and 338C received the same amount of feed, suggesting that the increase of DM and N digestibility was mainly related to the reduced feeding level in hot conditions.…”
Section: Discussionsupporting
confidence: 52%
“…For instance, while each degree increase in ambient temperature between 24 and 30 °C would induce a feed intake decrease of 50 g d −1 in pigs of 60 kg BW, the corresponding decrease would average 80 g d −1 in pigs of 90 kg BW. The principle of the reduction in feed intake as a response to reduce heat production (or reduce the thermic effect of feeding) has been consistently confirmed through calorimetry studies performed in respiration chambers either in pigs of 20-30 kg (Collin et al, 2001) or pigs of 50-60 kg BW (Renaudeau et al, 2013).…”
Section: Voluntary Feed Intake and Growth Performancementioning
confidence: 91%